Intervensi Non-Farmakologis pada Pasien dengan Sindroma Kelelahan Kronis: Literature Review - Bambang Aditya Nugraha; Sulastini; Sandra Pebrianti; Iwan Shalahuddin (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2023)
Introduction: Fatigue in Chronic Fatigue Syndrome (CFS) can reduce productivity and quality of life. Thus, it becomes important to identify non-pharmacological interventions to overcome fatigue in patients with CFS. Purpuse: identify non-pharmacological interventions in patients with chronic fatigue syndrome. Methods: This research is a narrative review. The literature sources used in the article search process include Science Direct, Springer Link and PubMed in the last 9 (nine) years (2014-2023). Article searches were carried out using English, namely ((chronic fatigue syndrome) AND (intervention)) AND (non-pharmacologic)). The inclusion criteria used in this literature review include full-text articles, articles in English, the year the article was published in the last 9 years (2014-2023) with a randomized control trial research design. Result: a total of 5 articles that matched the search focus, 2 articles from the Science Direct database, 1 article from Springer Link and 2 articles from PubMed. Conclusion: direct and indirect moxibustion, cupping, acupuncture, physical exercise have the potential to reduce fatigue in patients experiencing chronic fatigue syndrome. Health workers are expected to carry out further research regarding the application of non-pharmacological interventions found in this research to be applied in their respective contexts and settings.